Professionalism of political education and educations à - Ziegler, Béatrice (Swiss Journal of Educational Research, 2020)
The paper shows how civic/citizenship education defines the abilities of individuals to participate in (political) society in a self-determined and competent way. The discussion about competencies and concepts will be presented. It will also explain which principles civic/citizenship education regards as indispensable. As a result, aspects of interdisciplinary approaches of civic/citizenship education within the framework of éducations à will be discussed, and the possibilities of building up competencies will be addressed.